2002
DOI: 10.1051/0004-6361:20021560
|View full text |Cite
|
Sign up to set email alerts
|

The stellar activity-rotation relationship revisited: Dependence of saturated and non-saturated X-ray emission regimes on stellar mass for late-type dwarfs

Abstract: Abstract. We present the results of a new study on the relationship between coronal X-ray emission and stellar rotation in late-type main-sequence stars. We have selected a sample of 259 dwarfs in the B − V range 0.5-2.0, including 110 field stars and 149 members of the Pleiades, Hyades, α Persei, IC 2602 and IC 2391 open clusters. All the stars have been observed with ROSAT, and most of them have photometrically-measured rotation periods available. Our results confirm that two emission regimes exist, one in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

103
985
5
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 792 publications
(1,095 citation statements)
references
References 47 publications
103
985
5
2
Order By: Relevance
“…The X-ray emission from late-type stars in open clusters exhibits two kinds of dependences on stellar rotation (e.g. Patten & Simon 1996;Randich 2000;Feigelson et al 2003;Pizzolato et al 2003). Fast rotators show a relatively constant X-ray to bolometric luminosity ratio at the so-called (L X /L bol ) ≈ 10 −3 saturation level.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray emission from late-type stars in open clusters exhibits two kinds of dependences on stellar rotation (e.g. Patten & Simon 1996;Randich 2000;Feigelson et al 2003;Pizzolato et al 2003). Fast rotators show a relatively constant X-ray to bolometric luminosity ratio at the so-called (L X /L bol ) ≈ 10 −3 saturation level.…”
Section: Introductionmentioning
confidence: 99%
“…Using such proxy it has been shown that magnetic activity increases with rotation rate and that above a given rotation rate (that depends on the stellar spectral type but is around Ros ∼ 0.1), stellar magnetic activity first saturates (Pizzolato et al 2003;Wright et al 2011) and then possibly "over-saturates" for extremely fast rotation rate such as the ones found in young solar-like T-Tauri stars (Feigelson and Montmerle 1999). One can thus simply seek to characterize how the saturation of the dynamo generated field can be linked to the saturation of solar-like star X-ray emissivity.…”
Section: Nonlinear Dynamo Effect Magnetic Activity and Cyclesmentioning
confidence: 99%
“…Moreover, the measured widths of the coronal forbidden lines are generally close to their thermal values (FWHM 40-90 km s −1 at T∼10 6.2 -10 7.0 K), except for some of the fastest rotating stars in the observed sample (AB Dor, 31 Com, and the G1 star of Capella) all showing broadening exceeding the convolution between the thermal and the rotational widths, consistently with excess turbulence or with emitting regions at ∼0.4-1.3 stellar radii from the photosphere. Right: X-ray to bolometric luminosity ratio vs. empirical Rossby number including field dwarfs (crosses) and cluster stars (squares) (from Pizzolato et al 2003).…”
Section: Hi-res Spectroscopy Of Coronal Plasmamentioning
confidence: 99%
“…Figure 3). Pizzolato et al (2003) have demonstrated that the critical rotation period, below which saturation occours, increases with decreasing stellar mass, suggesting that the X-ray emission in late-type main sequence stars can be considered as an effect depending on the properties of the convective region as well as an effect depending on the total energy budget available in the star.…”
Section: X-ray Emission From Coronaementioning
confidence: 99%